Hydroponic fodder production technology for sustainable animal feed production - Mohapatra, Arpita; Panigrahy, Shakti Ranjan (Indian Farming, 2024)
In April 2023, India surpassed China to become the world’s most populous country. This population growth contributes to challenges such as the depletion and degradation of natural resources like soil and water due to urbanization and industrialization. However, India has the largest livestock population globally, leads in milk production, ranks third in egg production, and eighth in meat production. These animal products are crucial for food security and income support of the country. The vast animal population also compete with growing human population for space and other resources. This highlights a complex dynamics where increased animal population strains and as well as supports country’s agro-based food systems. It is quite challenging to provide balanced nutrition to such a vast animal base, especially in the background of scarce natural resources (soil and water), without which, human being will not get right kind of food for their survival and growth. Hydroponic is a method to produce sprout cereal plants without soil which can also be used as food and fodder crop. In case of livestock, it offers resource efficient and sustainable fodder to uphold the livestock productivity. The highly nutritious nature of hydroponic fodder and its minimal input requirement make it a befitting option for animal nutrition in future climate change challenges.